Mesolithic Settlement in the North Sea Basin A Case Study from Howick, North-East England - Waddington, Clive (Historic England, 2007)
The archaeological remains at Howick consist of a Mesolithic hut site and an Early Bronze Age cist cemetery located on a modern cliff edge overlooking a small estuary. This volume is devoted solely to the reporting and interpretation of the Mesolithic remains. Three huts had been constructed on the Howick site, all on the same footprint, with no evidence to indicate a gap between these occupations, and the remains inside the hut were all consistent with its use as a habitation site. The lithic material from Howick is the most accurately dated assemblage from any British Mesolithic site and is a classic example of a narrow-blade industry. Typically for Britain these sites date from around 7500 cal BC but the Howick dates indicate an earlier start for this type of industry. The chipped stone assemblage from Howick is all made from locally occurring beach pebble flint which fits into the wider pattern of localised raw material acquisition by groups elsewhere in North-East England.